The spatio-temporal partitioning of sperm by males of the prospermatogenic parasitoid Nasonia vitripennis is in line with its gregarious lifestyle. (August 2016) - Chirault, Marlène; Van de Zande, Louis; Hidalgo, Kevin; Chevrier, Claude; Bressac, Christophe; Lécureuil, Charlotte
Highlights: In Nasonia vitripennis spermatogenesis takes place before emergence. Spermatozoa are stored in testes before being transferred to the seminal vesicles. Spermatozoa are partitioned over successive copulations. Abstract: Male fitness depends on the number of lifetime progeny of their mates and could be constrained by the chance of finding a mate, lifespan and temporal patterns of sperm production and allocation. Here, we used the parasitic wasp Nasonia vitripennis with a two-week lifespan and a gregarious lifestyle, to analyze how the reproductive system is organized to allocate spermatozoa over consecutive matings. Results show that spermatogenesis is synchronized and completed one day before emergence so that males emerge with a full sperm complement. We also found a regulation of spermatozoa transfer between testis and seminal vesicles that allows males to partition small ejaculates over multiple matings. Overall, this study shows that for N. vitripennis, male fertilization potential is determined (1) at the pupal stage, when spermatogenesis takes place to generate a complete life-long stock, (2) on emergence, when transport of spermatozoa from testes to seminal vesicles is initiated and (3) in adulthood, during which spermatozoa are partitioned over successive copulations. Such life history-traits are consistent with the gregarious lifestyle of N. vitripennis .